Moderate hypothermic circulatory arrest in total arch repair for acute type A aortic dissection: clinical safety and efficacy - Gong, Ming; Ma, Wei-Guo; Guan, Xin-Liang; Wang, Long-Fei; Li, Jia-Chen; Lan, Feng; Sun, Li-Zhong; Zhang, Hong-Jia (Journal of Thoracic Disease, 2016)
Background: Continued debates exist regarding the optimal temperature during hypothermic circulatory arrest (HCA) in aortic arch repair for patients with type A aortic dissection (TAAD). This study seeks to examine whether the use of moderate HCA in emergency aortic arch surgery provides comparable operative outcomes to deep HCA for patients with acute TAAD. Methods: We prospectively enrolled 74 consecutive patients (mean age 47.7±9.8 years, 54 males) with acute TAAD, who underwent emergency total arch replacement and frozen elephant trunk implantation under HCA (18–28 ℃) with unilateral selective antegrade cerebral perfusion (uSACP). Patients were divided into two groups based on the nasopharyngeal temperature at the initiation of HCA: deep HCA (DHCA, 0.05). The temporal trend in the changes of postoperative levels of creatinine, aspartate aminotransferase, total bilirubin and lactate did not differ between two groups (P>0.05). Multivariate analysis found that the temperature during HCA (MHCA vs. DHCA) did not affect operative mortality, morbidities and neurologic complications. Instead, CPB time (in minutes) was the risk factor for operative mortality (odds ratio, 1.032; 95% confidence interval, 1.004–1.061; P=0.023). Conclusions: Moderate HCA is associated with equivalent operative mortality and morbidity and visceral organ functions compared to deep HCA in patients with acute TAAD undergoing total arch replacement under uSACP. This study implies the clinical safety and efficacy of moderate HCA in emergency aortic arch repair for such patients, which provides equivalent cerebral and visceral organ protection while decreasing CPB and cross-clamp times without increasing the risk of operative mortality and morbidity.